Here's the question you clicked on:
Calcmathlete
GIven that \(f(x) = \sqrt{9 - x^2}\), and that \(g(x) = f(x - 4)\), rewrite g(x) in terms of x. Please tell me how to do it and not just the answer.
\[g(x)=f(x-4)\]Notice that\[f(x-4)=\sqrt{9-(x-4)^2}\] Follow so far?
|dw:1344985583558:dw|
Oh...so you plugged in f(x - 4) which is formed by plugging in (x - 4) for x in f(x)?
Yup\[g(x)=f(x-4)=\sqrt{9-(x-4^2)}\]
So it would be: \[g(x) = \sqrt{-x^2 + 8x - 7}~?\]
Yes you could simplify it further to what you did,. Just another example: If it was \[g(x)=f(x+5x^2)\] Then:\[g(x)=f(x+5x^2)=\sqrt{9-(x+5x^2)^2}\]
Oh I get it...but for more practical uses, it would be just left as \[g(x) = \sqrt{9 - (x - 4)^2}~?\]
That's how I would leave it, unless your professor told you otherwise
Alright. THank you :) Just needed a quick refresher since I forgot how to do these momentarily!